Pott’s disease in upper thoracic vertebrae in atwo-year-old boy: Case report - Cortez-Bazán, Nathaly (2018)
Pott’s disease is a health problem in developing countries and its diagnosis in children is a challenge. Here we present the case of a two-year-old boy with Pott’s disease involving T1 to T3 thoracic vertebrae. The clinical presentation was characterized by difficulty walking, fever, cough, and dyspnea. At physical examination, kyphosis and bony prominence were observed in the cervicodorsal area. A positive tuberculin test was obtained, and Mycobacterium tuberculosis was isolated via culture of the gastric aspiration sample. The spine MRI showed a chronic abscess, destruction of two vertebrae, and bone marrow compression. The patient experienced some improvement with anti-TB therapy. Here, we emphasize the importance of giving consideration to the clinical suspicion for the early detection of this condition, as well as a quick TB-treatment start so as to avoid the disability and mortality associated to this disease.